Fabrication of plasmonic silver nanoparticle arrays by laser-induced dewetting of commercial silver paste. (15th April 2019) - Kim, Joon Ki; Lee, Kang Sup; Park, Tae-Hyeon; Jeong, Dong-Won; Kim, Zee Hwan; Jang, Du-Jeon
Graphical abstract: Highlights: Silver nanoparticle arrays were produced via laser-induced dewetting of silver paste. The first laser scan produced intermediate silver nanostructures. The second laser scan transformed the intermediate structures into the arrays. Silver nanoparticle arrays generated numerous hot spots to show strong SERS signals. Our fabrication method of laser-induced dewetting is facile and scalable. Abstract: Highly dense plasmonic silver nanoparticle (NP) arrays have been fabricated by laser-induced dewetting of commercially available silver paste as a starting bulk material. Laser-irradiation criteria for the laser melting, dewetting, and ablation of silver paste films have been determined in order to understand the optimal conditions of laser fabrication. The first laser-scan mode has produced unprecedented intermediate structures, so called laser-induced fine silver nanostructures (LIFSNs) while the second laser-scan mode has transformed LIFSNs into plasmonic silver NP arrays via the dewetting of the priorly formed nanostructures. The laser-induced fabrication of silver NP arrays has been found to be very sensitive to distance from secondly irradiated laser pulses, suggesting that the fine control of laser intensity is very important. Silver NP arrays of sub-100 nm diameters with narrow size distribution have been fabricated well at a laser scanning rate of ≥50 μm/s. As-prepared silver NP arrays have generated numerous hot spots to show highly strong surface-enhanced Raman scattering signals; the Raman enhancement factor of silver NP arrays for rhodamine 6G has been found as 1.2 × 10 6 . Overall, our fabrication method of plasmonic silver NP arrays via laser-induced dewetting is facile, scalable, and reproducible.